Operating Speed Prediction Models for Tangent Segments: A Brief Review - Musab AbuAddous (Salehan Institute of Higher Education, 2021)
This paper provides a review of studies aimed at developing operating speed prediction models for road tangent sections. The review included many studies, conducted in different geographical areas of the world, in terms of road classification, types of vehicles, techniques and devices used in data collection, number of study sites, the principle adopted in extracting the free-flow speed, as well as the topography that the road path passes through and grads of the studied sections. Moreover, this review mentioned the analysis methods adopted in the modeling, and included the model formulas that the researchers have reached in their studies, as it showed all the geometric elements and traffic characteristics that appeared in the models as independent variables. The author has avoided critiquing or evaluating the methodologies of the reviewed research and accordingly this paper has been prepared for documentation only. The author aims primarily to save the effort and time of graduate students and researchers interested in modeling the operating speed on straight segments, as all data and information are arranged in tables and coordinated for this purpose. Doi: 10.28991/cej-2021-03091784 Full Text: PDF